Literary Significance and Cultural Relevance of Selected Ilokano Short Stories (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
Literature reflects human life, capturing our experiences across time – past, present, and future.  However, local literature has faced a decline in interest among young readers, possibly due to a focus on famous national and international works in classrooms.  To address this, a study delved into Ilokano short stories.  These stories were carefully examined to understand their artistic value and relevance to current society. The study's approach involved analyzing the stories using different methods from literary criticism.  It looked closely at six Ilokano short stories written between the 1990s and early 2000s.  These stories, including titles like "Desparecidos"(Disappearance), "Jimmy Boy," “Anniniwan iti Likudan ti Arado (Shadow Behind the Plow), Voice Tape, “Addakanto Koma iti Panagturposko” (I Wish to See You in My Graduation Day), and Ama Anib (Father Anib) covered various themes. The results of this analysis highlighted two essential aspects of these stories.  First, they aligned with key elements of literary work, incorporating symbols that conveyed societal issues.  The stories symbolically tackled topics like supporting the disadvantaged, navigating dreams and reality, economic disparities, and the significance of family. Moreover, these stories painted a vivid picture of Ilokano values.  They showcased strong family bonds, resilience, determination to chase dreams, and the fight for justice and freedom. These insights made it clear that Ilokano literature shares qualities with national and international literary standards.  The prominence of the Ilokano language also spoke to its potential as a language for education, science, and business.  This led to a recommendation to incorporate these stories into school curricula, possibly translated into English or Filipino for broader reach. By taking these steps, the rich tapestry of Ilokano literature could spread across education and culture, bridging tradition and the contemporary world.
Keywords: literary criticism; discourse analysis; Ilokano short stories